APPRAISAL OF DIFFERENT PLANT PRODUCTS AGAINST TROGODERMA GRANARIUM EVERTS TO PROTECT STORED WHEATA LABORATORY COMPARISON - Sarwar, M.; Sattar, M. (The Nucleus, 2012)
Laboratory study was initiated to analyze various locally available botanical materials such as Chenopodium album L. (White goosefoot), Cichorum intybus L. (Chicory) and Meliolotus parviflora L. (Honey clover) applied at the rate of 2 percent into wheat grain for the control of Trogoderma granarium Everts (Coleoptera: Dermestidae). After data computation on the basis of fixed parameters, it was observed that all natural protectants used had shown potentiality in controlling T. granarium as these proved very effective compared to no pesticide application treatment. It is worthwhile to mention that among various products tested, C. intybus powder showed the best results to control pest, approached by C. album and M. parviflora treatments as compared to untreated kernels. The results of this findings show that natural protectants used in the study could be useful and desirable tools in stored wheat pest management plan.